2020
DOI: 10.11648/j.ijcts.20200602.13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Self-care Practice, and Associated Factors Among Hypertensive Patients the Public Hospital of Addis Ababa Ethiopia 2016 G.C.

Abstract: Background: Patients with hypertension are a high risk of cardiovascular disease. An increase of 10 mmHg (more than normal) in diastolic blood pressure leads to a relatively increased risk of stroke and cardiovascular disease by 37%. Moreover, hypertension may impair vision. The symptoms range from blurred vision to blindness. A lack of knowledge about hypertension negatively influences patients' awareness and behaviors and is a major obstacle in controlling hypertension. The general objective of the study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In this study, 54.1% of hypertension patients had good self-care practice towards hypertension. It is consistent with a study done in Addis Ababa (51%) [ 19 ] and Dessie Town (49%) [ 18 ]. On the contrary, self-care practice in this study is higher than studies conducted in Tigray with 23% [ 12 ] and in Harar town with 29% [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, 54.1% of hypertension patients had good self-care practice towards hypertension. It is consistent with a study done in Addis Ababa (51%) [ 19 ] and Dessie Town (49%) [ 18 ]. On the contrary, self-care practice in this study is higher than studies conducted in Tigray with 23% [ 12 ] and in Harar town with 29% [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study was supported by the study conducted in Addis Ababa. Living in urban areas was three times more likely to adapt to good self-care practice [ 19 ]. The possible reason is that living in urban area was near information and media access to hypertension control and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was higher than that of studies done in Mekele (20.3%) [ 41 ], South Ethiopia (24%) [ 22 ], and Debre Berhan (24%) [ 42 ]. On the contrary, this finding was lower than studies conducted in Nekemte (68.92%), Gondar (59.4%), Debre Tabor (54.1%) [ 25 ], Harar (62.1%) [ 43 ] Addis Ababa (51%) [ 44 ], Dessie (49%) [ 26 ], Saudi Arabia (74.4%) [ 24 ] and South India (60.6%) [ 45 ]. This inconsistency could be explained by variations in sample size, socioeconomic and cultural differences, levels of understanding of hypertension and its management, differences in the methods and tools used to gather the data, and the methodological disparities between studies.…”
Section: Discussionmentioning
confidence: 73%
“…This outcome is supported by another study [19] who showed a significant correlation between age and patients' awareness of HTN. Furthermore, [20] showed significant associations between the knowledge, and occupation of the respondents respectively. Likewise, another study [21] exposes a significant association between employment and patient awareness of HTN.…”
Section: Discussionmentioning
confidence: 90%